Business Performance Determination Mediated by Innovation Capabilities in New Independent Workers: Analysis of Self-Efficacy, Financial Literacy, and Strategic Partnerships - Safitri Siswono; Sri Widyastuti; Tri Widyastuti (Dinasti Publisher, 2026)
This study examines the influence of self-efficacy, financial literacy, and strategic partnerships on business performance, with innovation capability acting as a mediating variable among new independent workers at the Ministry of Manpower of the Republic of Indonesia. The research applies a quantitative descriptive design using a survey approach to collect data from respondents. The analysis is conducted using Structural Equation Modelling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The findings indicate that self-efficacy significantly and positively influences innovation capability, suggesting that individuals with greater confidence in their abilities are more likely to develop innovative ideas and practices in their businesses. Financial literacy also shows a positive and significant effect on innovation capability, highlighting the importance of financial knowledge in supporting innovative business activities. However, strategic partnerships do not significantly affect innovation capability. In terms of business performance, self-efficacy, financial literacy, strategic partnerships, and innovation capability, each demonstrates a positive and significant impact. Furthermore, innovation capability successfully mediates the relationship between self-efficacy and business performance as well as between financial literacy and business performance. Conversely, innovation capability does not mediate the relationship between strategic partnerships and business performance in this study.